PREVALENSI PENDERITA LUTS YANG DISEBABKAN BPH DI PUSKESMAS TUMINTING, PUSKESMAS WONASA, PUSKESMAS PANIKI, PUSKESMAS TIKALA, PUSKESMAS BAHU KOTA MANADO TAHUN 2015 - Palit, Belva M.; Monoarfa, Alwin; Wowiling, P. A.V (e-CliniC, 2016)
Abstract: Lower urinary tract symptoms (LUTS) often occur in elderly population. One of the causes of LUTS in aged males is benign prostatic hyperplasia (BPH). Males with severe LUTS will suffer from decreased libido, difficulty in maintaining an erection, and decreased level of sexual satisfaction. The severity of LUTS was scored by using the International Prostatic Symptom Score (IPSS) is recommended by the World Health Organization (WHO). This study was aimed to determine the prevalence of LUTS in several primary health centers (PHC) in Manado in 2015. This was a descriptive prospective study using data of several health centers in Manado in 2015. The results showed the prevalences of LUTS at several PHC were as follows: Wonasa 6 cases (19%), Tuminting 9 cases (28%), Paniki 4 cases (13%), Tikala 6 cases (19%), and Bahu 7 cases (22%). LUTS were most common at the age of 60-69 years.Keywords: LUTS, BPH, IPSS scoreÂ Abstrak: Lower Urinary Tract Symptom (LUTS) sering terjadi pada populasi usia lanjut. Salah satu penyebab yang paling sering ialah benign prostatic hyperplasia (BPH). Laki-lakidengan LUTS yang berat akan mengalami penurunan libido, kesulitan mempertahankan ereksi, dan penurunan tingkat kepuasan seksual. Untuk menilai tingkat keparahan dari LUTS digunakan sistem skoring International Prostatic Symptom Score (IPSS). Penelitian ini bertujuan untuk mengetahui prevalensi penderita LUTS di beberapa puskesmas Kota Manado tahun 2015. Jenis penelitian ialah deskriptif prospektif dengan mengambil data di beberapa puskesmas Kota Manado tahun 2015. Hasil penelitian menunjukan prevalensi penderita LUTS di Puskesmas Wonasa 6 kasus (19%), Puskesmas Tuminting 9 kasus (28%), Puskesmas Paniki 4 kasus (13%), Puskesmas Tikala 6 kasus (19%), dan Puskesmas Bahu 7 kasus (22%). Penderita LUTS tersering muncul pada usia 60-69 tahun. Kata kunci: LUTS, BPH, skor IPSS